Decomposing the Scene: : gender, community, race, and dance as a contact zone in Mimosa / Twenty Looks or Paris is Burning - Lodi Rizzini, Stefania (Revista Brasileira de Estudos da Presença, 2025)
This article explores dance through the lens of gender, using the case study of Mimosa/Twenty Looks or Paris is Burning, a collective performance conceived by four of the most important contemporary choreographers: Trajal Harrell, Cecilia Bengolea, François Chaignaud, and Marlene Monteiro Freitas. This text interrogates different elements highlighted by this performance, such as how dance heritage may dialogue with contemporary perspectives concerning class, gender, and race issues, to help us better understand the representation of subcultural identity in dance.